Immunoglobulin Therapy in a Patient With Severe Chikungunya Fever and Vesiculobullous Lesions - Fernandes, Ana Isabel V.; Souza, Joelma R.; Silva, Adriano R.; Cruz, Sara B. S. C.; Castellano, Lúcio R. C. (Frontiers in Immunology, 2019)
Chikungunya virus (CHIKV) is an emerging arbovirus whose transmission has already been reported in several countries. Although the majority of individuals acutely infected with CHIKV appear to become asymptomatic, reports showing the occurrence of atypical and severe forms of the disease are increasing. Among them, the neurological and skin manifestations require medical attention. Treatment of CHIKV infection is almost symptomatic. In this sense, we report the case of a 56-years-old man who presented fever, headaches, paresthesia and pain in the right arm with visible red spots on the skin starting 30 days before Hospital admission. Tests determined Chikungunya infection and excluded other co-morbidities. Disease evolved with edema in hands and feet and extensive hemorrhagic bullous lesions on the skin of upper and lower limbs. Variations in hematological counts associated with liver dysfunction determined this patient's admission to the Intensive Care Unit. Then, he received intravenous antibiotic and immunoglobulin therapy (400 mg/Kg/day for the period of 5 days) with total recovery from the lesions after 10 days of follow-up. A general improvement in blood cell count and successful wound healing was observed. After discharge, no other clinical sign of the disease was reported until nowadays. This case reports for the first time the successful administration of intravenous immunoglobulin therapy to a patient with severe atypical dermatological form of Chikungunya Fever without any associated comorbidity.